Microencapsulation of Cassia Alata extract into biodegradable PLGA - Alfatama, Mulham; Ahmad, Kausar; Doolaanea, Abd Monem; Ali, Aimen Abdo Elsaid; Ismail, Ahmad Fahmi Harun; Mohamed, Farahidah (2011)
Senna alata or Cassia alata (C. Alata) is a plant belonging to the family Leguminosae and it has antifungal and antimicrobial activities.This research aims to extract Cassia alata using known extraction procedure, followed by microencapsulation using biodegradable Poly (lactide-co-glycolide) (PLGA). The microencapsulation is envisaged to release the extract in a controlled manner. For microsphere fabrication, aqueous extract of C. alata was added to PLGA solution, previously dissolved in DCM, and was homogenized to form the primary water-in-oil (w/o) emulsion. This w/o emulsion was immediately injected into 1% aqueous PVA and homogenized to form the secondary water-in-oil-in-water (w/o/w) emulsion. The w/o/w emulsion was then transferred to a continuously stirred hardening tank of 1% aqueous PVA and the stirring was continued for 2 hours to allow complete evaporation of DCM. The hardened microspheres were collected by centrifugation, washed and freeze-dried. Resultant microspheres were characterized for size distribution and external morphology by laser sizer diffraction technique and scanning electron microscopy, respectively. Encapsulation efficiency(EE) was also calculated and the C. alata was quantified by UV absorbance. Several parameters have been investigated including several types of surfactants, water to oil ratios and buffer systems. It was found that, most of the surfactants employed resulted in low EE (<10%), however with 3% poly vinyl alcohol (PVA), gave slightly higher EE of 11%, with size distribution of 7-13 µm. The EE (50%) was significantly improved when the hardening tank is buffered to pH 7, with minimal effect on particle size.